Etika dan Hukum dalam Penggunaan Teknologi Pengawasan Digital oleh Negara: Ethics and Law in the Use of Digital Surveillance Technology by States - Alisha Elvis; Lita Estyawati; Lutfiah Sholikhatun Nafi’ah (Litera Academica Publishing, 2025)
The use of digital surveillance technology by the state continues to increase along with advances in information technology and the need for national security. However, this practice raises complex ethical and legal issues, particularly related to the right to privacy, freedom of expression, and the potential for abuse of power. This article aims to analyze the ethical dilemmas and legal basis in the application of digital surveillance technology by the state, using a normative approach and case studies in several countries, including Indonesia. The discussion focuses on the limitations of state authority in conducting surveillance, testing the principles of proportionality and accountability, and the importance of regulations that protect civil rights in the digital era. The results of the study show that although digital surveillance can increase the effectiveness of law enforcement and security, its use must be strictly limited by transparent laws and independent oversight mechanisms. This article recommends the establishment of a national legal framework that balances security interests and human rights protection, in order to prevent repressive surveillance practices in the digital era.